Calculation of axial loads on columns by tributary area method and finite element method - Tee Chin Fang (School of Environmental Engineering, University Malaysia Perlis, 2014)
The basic concept for structural analysis is transfer the service loading to the support that nearby. Axial load are transfer from building structure to the column and at the end transfer to foundation. Base on this study, the main purpose is to analyze the axial loadings that transmit to column by using tributary area method and compare with the analysis using finite element method.